2019
DOI: 10.1136/bmjoq-2018-000596
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care during childbirth at public health facilities in Bangladesh: a cross-sectional study using WHO/UNICEF ‘Every Mother Every Newborn (EMEN)’ standards

Abstract: BackgroundThis manuscript presents findings from a baseline assessment of health facilities in Bangladesh prior to the implementation of the ‘Every Mother Every Newborn Quality Improvement’ initiative.MethodologyA cross-sectional survey was conducted between June and August 2016 in 15 government health facilities. Structural readiness was assessed by observing the physical environment, the availability of essential drugs and equipment, and the functionality of the referral system. Structured interviews were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 38 publications
6
19
3
Order By: Relevance
“…Interestingly, the bottlenecks identified through qualitative exploration were not uncommon. In different studies, the same bottlenecks were found which have been aggravated in our study on account of the remoteness of the study sites [ 9 , 31 34 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, the bottlenecks identified through qualitative exploration were not uncommon. In different studies, the same bottlenecks were found which have been aggravated in our study on account of the remoteness of the study sites [ 9 , 31 34 ].…”
Section: Discussionsupporting
confidence: 81%
“…It is also worth mentioning that even many designated emergency obstetric care (EmOC) facilities are not functioning in Bangladesh because of human resources and logistics issues, let alone these HtR facilities [ 30 ]. A recent research conducted in Kurigram, a district of this study, found similar results for the service provision in the facilities [ 31 ].…”
Section: Discussionsupporting
confidence: 79%
“…A recent study in Bangladesh reported oxytocin administration was suboptimal at 94% of district hospitals and 71% of sub-district hospitals [9]. The BMMS 2016 data also shows that only 41% of public hospitals quali ed as functional CEmOC facilities [2].This means that the majority of facilities are not fully compliant with CEmOC and AMSTL protocols.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study in Bangladesh reported oxytocin administration was suboptimal at 94% of district hospitals and 71% of sub-district hospitals [6]. The BMMS 2016 data also shows that only 41% of public hospitals quali ed as functional CEmOC facilities [1].This means that the majority of facilities are not fully compliant with CEmOC and AMSTL protocols.…”
Section: Resultmentioning
confidence: 99%